Chip (Ldb1) is a putative cofactor of Zelda forming a functional bridge to CBP during zygotic genome activation. - Galouzis, C.C.; Kherdjemil, Y.; Forneris, M.; Viales, R.R.; Marco-Ferreres, R.; Furlong, E.E.M. (Molecular Cell, 2025)
The cofactor LIM-domain-binding protein 1 (Ldb1) is linked to many processes in gene regulation, including enhancer-promoter communication, interchromosomal interactions, and enhanceosome-cofactor-like activity. However, its functional requirement and molecular role during embryogenesis remain unclear. Here, we used optogenetics (iLEXY) to rapidly deplete Drosophila Ldb1 (Chip) from the nucleus at precise time windows. Remarkably, this pinpointed the essential window of Chip's function to just 1 h of embryogenesis, overlapping zygotic genome activation (ZGA). We show that Zelda, a pioneer factor essential for ZGA, recruits Chip to chromatin, and both factors regulate concordant changes in gene expression, suggesting that Chip is a cofactor of Zelda. Chip does not significantly impact chromatin architecture at these stages, but instead recruits CBP, and is essential for H3K27ac deposition at enhancers and promoters, and for the proper expression of co-regulated genes. These data identify Chip as a functional bridge between Zelda and the coactivator CBP to regulate gene expression in early embryogenesis.